2021
DOI: 10.21203/rs.3.rs-193946/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Review on Sewage Sludge Valorization via Hydrothermal Carbonization and Applications for Circular Economy

Abstract: In pursuit of establishing a circular economy, waste-to-energy approach is gaining increasing attention. In this manner valorization of sewage sludge constitutes a critical importance due to generation in high quantities, difficulties in disposal and associating environmental impacts. Hydrothermal carbonization (HTC) is a relatively recent, however acclaimed method for sewage sludge management and valorization due to process compliance with sludge characteristics. In this review, research studies are evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
0
0
0
Order By: Relevance
“…At the same time, the hydrochar has higher carbon and lower volatile content, and has higher combustion quality than sewage sludge. Furthermore, Cebi et al [21] reported that hydrochar derived from sewage sludge has lignite-like fuel properties. Experiments combining sewage sludge hydrochar with coal samples of different properties showed more stable combustion conditions, improved fuel quality, and reduced emissions.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the hydrochar has higher carbon and lower volatile content, and has higher combustion quality than sewage sludge. Furthermore, Cebi et al [21] reported that hydrochar derived from sewage sludge has lignite-like fuel properties. Experiments combining sewage sludge hydrochar with coal samples of different properties showed more stable combustion conditions, improved fuel quality, and reduced emissions.…”
Section: Introductionmentioning
confidence: 99%